PERANCANGAN USER INTERFACE DAN USER EXPERIENCE APLIKASI PENJUALAN HIJAB PADA VEE HIJAB MENGGUNAKAN METODE DESIGN THINKING - Adven Bintang Putra Pratama; Indrawan Ady Saputro (PT. Hasba Edukasi Mandiri, 2026)
The rapid growth of the modest fashion industry in Indonesia has driven retail businesses such as Vee Hijab to transform from manual, chat-based sales systems into structured mobile-based e-commerce applications. Previously, customer transactions conducted via instant messaging faced various operational hurdles, including repetitive manual inquiries regarding color variants, fabric sizes, stock availability, and real-time shipping status, which ultimately degraded the user shopping experience and reduced sales conversion rates. This research aims to design an intuitive, responsive, and user-centered User Interface (UI) and User Experience (UX) for the Vee Hijab mobile application using the Design Thinking method. The Design Thinking framework comprises five sequential phases: Empathize, Define, Ideate, Prototype, and Test. In the prototype phase, a high-fidelity interactive prototype consisting of 28 core screens categorized into 7 functional categories was developed, incorporating specialized features such as bottom-sheet color/size selection, real-time stock indicators, and interactive courier tracking. Evaluation was conducted through Usability Testing and the System Usability Scale (SUS) involving 30 target users. The testing results yielded an average SUS score of 84.5, which falls under the